In vitro antibacterial-antibiofilm effect of Hypericum atomarium Boiss and chemical composition (Brazilian Journal of Pharmaceutical Sciences, 2023)
Treatment with plant is considered an effective option against increased antibiotic resistance. In this study antibiofilm activity of methanol (CH3OH), chloroform (CHCl3), ethyl acetate (EtOAc) and water (H2O) extracts of Hypericum atomarium Boiss. which is member of Hypericum genus was evaluated in Pseudomonas aeruginosa PAO1 and antibacterial performance against Gram (+) and Gram (-) strains and also bioactive compounds of extract were analysed using by HPLC and GC-MS. According to antibacterial activity test results the extracts were effective all Gram (+) bacteria and Gram (-) Chromobacterium violaceum (MICs ranging from 0.42 μg/ml to 4.3 mg). Inhibition effect of biofilm formation was found to be different rate in extracts (methanol-63%, chloroform-52%). The major flavonoids were detected (−)-epicatechin (2388.93 μg/ml) and (+)-catechin (788.94 μg/ml). The main phenolic acids were appeared as caffeic acid 277.34 μg/ml and chlorogenic acid 261.79 μg/ml. And according to GC results α-pinene was found main compound for three solvent extracts methanol, chloroform and ethyl acetate 67.05, 62.69, 49.28% rate respectively.